Biogeographic partitioning of Southern Ocean microorganisms revealed by metagenomics. (30th November 2012) - Wilkins, David; Lauro, Federico M.; Williams, Timothy J.; Demaere, Matthew Z.; Brown, Mark V.; Hoffman, Jeffrey M.; Andrews‐Pfannkoch, Cynthia; Mcquaid, Jeffrey B.; Riddle, Martin J.; Rintoul, Stephen R.; Cavicchioli, Ricardo
Summary: We performed a metagenomic survey (6.6 Gbp of 454 sequence data) of Southern Ocean (SO) microorganisms during the austral summer of 2007–2008, examining the genomic signatures of communities across a latitudinal transect from Hobart (44°S) to the Mertz Glacier, Antarctica (67°S). Operational taxonomic units (OTUs) of the SAR11 and SAR116 clades and the cyanobacterial genera Prochlorococcus and Synechococcus were strongly overrepresented north of the Polar Front (PF). Conversely, OTUs of the Gammaproteobacterial Sulfur Oxidizer‐EOSA‐1 (GSO‐EOSA‐1) complex, the phyla Bacteroidetes and Verrucomicrobia and order Rhodobacterales were characteristic of waters south of the PF. Functions enriched south of the PF included a range of transporters, sulfur reduction and histidine degradation to glutamate, while branched‐chain amino acid transport, nucleic acid biosynthesis and methionine salvage were overrepresented north of the PF. The taxonomic and functional characteristics suggested a shift of primary production from cyanobacteria in the north to eukaryotic phytoplankton in the south, and reflected the different trophic statuses of the two regions. The study provides a new level of understanding about SO microbial communities, describing the contrasting taxonomic and functional characteristics of microbial assemblages either side of the PF.